An Overview of Selected Visual Illustrations in Elementary Literatures of Globalight Book Publishers, Ibadan, Nigeria - Funmilayo, Adesile Mercy (VCD: Journal of Visual Communication Design, 2024)
Improving elementary education is no doubt, key to attaining and sustaining a meaningful learned, and egalitarian society. Its fundamentals are embedded in the affective domain with a thrust in visual cognition, significantly in early childhood education. Affective illustrations particularly in pictures are argued to speak more than a thousand words. Interestingly, this assertion is presumably responsible for why Nigerian elementary books were proliferated with illustrational pictures in contemporary times. A development that is not only welcoming but has come to stay in Nigerian elementary education, owing to its value in terms of pupils' comprehension and illumination. As such, this paper examines selected books published by Globalight, Ibadan. The method adopted is bibliographical, shortlisting six of its plethora of publications to critical visualization; particularly from external, internal, topographical, and illustrational standpoints using design principles. The finding revealed adequacy of design elements, through some improvement, will go a long way in stimulating pupils’ learning potentials and tendencies.